Peningkatan Kesadaran Berinvestasi bagi Gen-Z sebagai Digital Native melalui Kegiatan Sosialisasi - Hernawati W Retno Wiratih; A.B.M. Witono; Ikramina Larasati Hazrati Havidz; M. Havidz Aima; Maya Puspita Dewi (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
Throughout 2021, the number of investors in the Indonesian capital, the Indonesian capital market, recorded the highest growth record in the 44-year history of the Indonesian capital market. The number of young investors investing in financial products, especially stocks in the capital market, has increased significantly amid the global pandemic. The stock market is driven by emotion and investors are driven by the fear of buying or selling stocks at the right time or the fear that they shouldn't buy or sell when they do. The community service is therefor held to bridge the current phenomena of invetment. The method applied was forum group discussion and lecturing given by speaker that expertise in the field of investment. Thus, the participants joined the webinar may enhance their knowledge on investment while encouraging their awareness on investment as well.